You Know What I’m Saying? - Fisher, Emily; Maniglio, Francesca (United States, 1998)
Soros Documentary Fund A South Bronx community fights to survive drug abuse, the spread of AIDS, and indifference. While documenting the community outreach activities of St. Ann's Corner of Harm Reduction, the film illustrates the many dimensions of harm reduction and human rights.